Sign-reversed anomalous nernst effect with matched Seebeck coefficient in lanthanide-iron alloys for the direct sensing of heat flux - Hyun Yu; Sang J. Park; Inho Lee; Ji Hoon Shim; Hyungyu Jin (Science and Technology of Advanced Materials)
Heat flux sensors based on the anomalous Nernst effect (ANE) have emerged as a promising solution for achieving thin and flexible designs. ANE-based heat flux sensors typically employ thermopile structures composed of two ANE materials with opposite signs, connected in series to enhance sensing performance. However, a mismatch in the Seebeck coefficient between the two ANE materials causes a considerable offset voltage due to the Seebeck effect (SE) under oblique heat flux. This parasitic sensing voltage hinders direct sensing of heat flux in the intended direction. In this study, a sign-reversed ANE with matched Seebeck coefficient is examined in Fe3Ln (Ln = Gd, Tb, Dy, Ho, and Er), enabling a thermopile structure free from the SE-induced offset voltage. Based on density functional theory calculations, Fe₃Ln is selected as a suitable candidate for exhibiting sign reversal of ANE while maintaining the Seebeck coefficient. At 300 K, Fe3Ln (Ln = Gd, Tb, Dy, and Ho) exhibits a positive ANE sign, whereas Fe3Er exhibits a negative ANE sign, facilitating the combination of two sign-reversed ANE materials. Among these, Fe3Ho and Fe3Er demonstrate the lowest Seebeck coefficient difference of 0.45 μV K−1, minimizing the offset voltage-induced relative uncertainty, as confirmed by COMSOL simulations – comparable to that of other SE-based heat flux sensors. This study paves the way for the development of ANE-based heat flux sensors by introducing a novel approach to pairing opposite-ANE-sign materials with matched Seebeck coefficient, enabling direct and accurate heat flux sensing via thermopile structures.